Occurrence of Rework on Components of Building Project in Lagos State, Nigeria - Ajayi, Oluwaseyi Modupe (International Journal of Sustainable Construction Engineering and Technology, 2017)
Rework is redoing an aspect of building work as a result of poor quality, wrong implementation, changes, and errors. The purpose of this study is to assess the frequency of occurrence of rework on the component of building projects in order to identify where the stakeholders needs to be careful to prevent re –doing the aspect of work. Literatures were reviewed on the sources, occurrence and effect of rework on building project components. Descriptive research design was used for this study and the population of the study was clients’, consultants and contractors within the construction industry. Simple random sampling technique was used to select the respondents, thus each respondent has equal chance of being selected. Ninety – eight (98) questionnaires were distributed and fifty – two (52) were returned given an average response rate of 52%. Statistical package for social sciences (SPSS) 21st version was used for analysis. Frequency, percentage, Mean Item Score, Ranking and Mann-Whitey test were statistical tools used to generate the results. Poor communication with design consultant, use of poor quality materials and poor workmanship were identified as causes of rework. Consultants are mostly responsible for rework of foundation, blockwork, staircase, tiling, sanitary fitting, electrical work and external work. In conclusion, management skill is necessary for reducing rework and for project performance level. Consultants should work together as a team to ensure productivity and profit margin.